I will not ever never eat a tomato : featuring Charlie and Lola - Child, Lauren. frey50 (London : Orchard, 2001)
A fussy eater decides to sample the carrots after her brother convinces her that they are really orange twiglets from Jupiter.
Originally published: 2000.
Keywords: Food habits -- Pictorial works -- Juvenile fiction; Children's stories -- Pictorial works